The effect of longer-term creatine supplementation on elite swimming performance after an acute creatine loading - Theodorou, A. S.; Cooke, C. B.; King, R. F.; Hood, C.; Denison, T.; Wainwright, B. G.; Havenetidis, K. (Journal of Sports Sciences, 1999)
We investigated the effect of an acute creatine loading (25 g per day for 4 days) and longer-term creatine supplementation (5 g of creatine or 5 g of placebo per day for 2 months) on the performance of 22 elite swimmers during maximal interval sessions. After the acute creatine loading, the mean of the average interval swim times for all swimmers (n = 22) improved (44.3 +/- 16.5 s before vs 43.7 +/- 16.3 s after supplementation; P < 0.01). Three of the 22 swimmers did not respond positively to supplementation. After 2 months of longer term creatine supplementation or placebo,neither group showed a significant change in swimming performance (38.7 +/-13.5 s before vs 38.7 +/- 14.1 s after for the creatine group; 48.7 +/- 18.0 s before vs 48.7 +/-18.1 s after for the placebo group). We conclude that, in elite swimmers, 4 days of acute creatine loading improves swimming performance significantly when assessed by maximal interval sessions. However, longer-term supplementation for 2 months (5 g of creatine per day) did not benefit significantly the creatine group compared with the placebo group.